The information coaches use to make team selection decisions: a scoping review and future recommendations - Fiander, M. F.; Stebbings, J.; Coulson, M. C.; Phelan, S. (Sports Coaching Review, 2023)
Selecting players for a team is one of the most important and recurring decisions sport coaches make. Despite this, relatively little is known about the information coaches use to make team selection decisions. In response to this, the following scoping review aims to (1) present literature that can offer insight into the information coaches use to make team selection decisions and (2) provide a platform from which researchers, practitioners and coaches can explore this often taken-for-granted decision. The systematic literature search was conducted following guidelines set out by PRISMA. Given the small number of studies found (N = 16), the extant literature fails to fully answer the question of why players are selected. Results are discussed in light of key theoretical approaches to decision-making (i.e. information processing, naturalistic decision-making and ecological psychology) to demonstrate the value of adopting each in specific instances to further our understanding of coaches` team selection decisions.